2013
DOI: 10.1098/rsta.2012.0190
|View full text |Cite
|
Sign up to set email alerts
|

Biotin-conjugated tumour-targeting photocytotoxic iron(III) complexes

Abstract: Iron(III) complexes [FeL(B)] ( 1 – 4 ) of a tetradentate phenolate-based ligand (H 3 L) and biotin-conjugated dipyridophenazine bases (B), viz. 7-aminodipyrido [3,2- a :2′,3′- c ]-phenazine (dppza in 1 ), ( N -dipyrido[3,2- a :2′,3′- c ]-phenazino)amidobiotin (dppzNB in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The cytotoxicity was measured from the IC 50 values (50 % inhibitory concentration) obtained from the cell‐viability assay. The complexes generally show significant photocytotoxicity in the cancer‐cell lines and are negligibly toxic in dark conditions (Table , Figures S12–S16) . The IC 50 values of the control complex 1 , in 400–700 nm light, are > 100 µ m in all of the cell lines.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The cytotoxicity was measured from the IC 50 values (50 % inhibitory concentration) obtained from the cell‐viability assay. The complexes generally show significant photocytotoxicity in the cancer‐cell lines and are negligibly toxic in dark conditions (Table , Figures S12–S16) . The IC 50 values of the control complex 1 , in 400–700 nm light, are > 100 µ m in all of the cell lines.…”
Section: Resultsmentioning
confidence: 98%
“…The values are taken from refs , . and are converted to µ m using the approximate molecular mass of Photofrin® (600 g mol –1 ); at 633 nm excitation with a fluence rate of 5 J cm –2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worthy of note, the same group also synthesized bimetallic Fe(III) complexes as PSs in view of DNA cleavage [46,47] and site specific protein cleavage [48]. Additionally, a recent publication by the same authors showed that the conjugation of a phototoxic Fe(III) complex to biotin allows for selective tumor delivery of the PDT agent [49]. In comparison to complexes with a +3 oxidation state, the studies of Fe complexes with a +2 oxidation state as a PS are scare.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, PLGA was chosen as the hydrophobic core for its biodegradable and biocompatible nature, along with its promising ability to encapsulate high amount of hydrophobic drugs (which has been approved by Food and Drug Administration [FDA] as the nanomaterial) 17 ; lecithin was selected as a monolayer around the PLGA core to enhance the encapsulation ability and biocompatibility of PLGA NP; DSPEePEGeCOOH could be inserted into the lecithin monolayer to form a PEG shell, then to enhance the stability of PLGA NP by producing both steric hindrance and electrostatic repulsion, and prolong the circulation time of PLGA NP in vivo; DSPE-PEG-biotin, a novel targeting ligand, was used for both active targeting of tumor cells thanks to the presence of biotin because biotin is a small molecular weight ligand known to target the sodium-dependent multivitamin transporter (SMVT) on the tumor cells, 18,19 and extending the duration in circulation system, thanks to the presence of PEG chains known to decrease the recognition by the immune system. 20 Profoundly, it has been reported that SMVT transporters are overexpressed in many tumor cells including HepG2 cells. [21][22][23] Thus, the cell experiments in this study were exerted on HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%